Una nueva especie de Kreodanthus (Orchidaceae‑Goodyerinae) del occidente de México y El Salvador - Gonzalez Tamayo, Roberto (Instituto de Ecología, A.C., 1995)
Kreodanthus casillasii is proposed as a new species. A comparative table is presented to distinguish this new species from K. secundus (Ames) Garay and K. ovatilabius (Ames et Correll) Garay, the last one being its closest relative.